Anterior knee pain as a potential risk factor for falls in older adults: insights from the osteoarthritis initiative data - Ting Xiong; Yanghuan Ou; Shenliang Chen; Shuaigang Liu; Xuan Yi; Xueqiang Deng; Tao Cheng; Liang Hao (BMC, 2023)
Abstract Background Knee joint pain has been demonstrated to be a separate risk factor for falling. A common pain site in the knee, anterior knee pain(AKP), is believed to be associated with early knee osteoarthritis (KOA).This study investigated the relationship between falls and AKP in people with or at risk for KOA. Methods Four years of follow-up data from the Osteoarthritis Initiative cohort trial, a large-scale, multicenter observational investigation, were analyzed in this study. A patellar quadriceps tenderness/tendinitis knee exam was performed to evaluate AKP. Falls were self-reported. The associations between falls (recurrent falls: ≥2 falls/year; any falls: ≥1 fall(s)/year) and AKP were analyzed using the generalized estimation equation of repeated logistic regression and adjusted for confounding variables. Results The study analyzed data from 3,318 participants, split into two groups: those with AKP (720 participants) and those without AKP (2,598 participants). The primary outcome of the study, which focused on repeated falls, revealed that participants with AKP were 1.27 times more likely to experience repeated falls compared to those without AKP (95% CI: 1.07-1.52, P = 0.007). However, when considering any falls experienced by an individual as an additional outcome, it is important to note that our findings did not indicate a significant predictive effect of AKP on any falls investigated. Sensitivity analyses, which excluded knee arthroplasty cases, yielded consistent results with the aforementioned findings. Conclusions Older adults with AKP experience a higher frequency of falls compared to those without AKP in individuals diagnosed with KOA or at a high risk of developing KOA.